FRAÏSSÉ LIMITS OF C*-ALGEBRAS. (29th June 2016) - EAGLE, CHRISTOPHER J.; FARAH, ILIJAS; HART, BRADD; KADETS, BORIS; KALASHNYK, VLADYSLAV; LUPINI, MARTINO
Abstract: We realize the Jiang-Su algebra, all UHF algebras, and the hyperfinite II1 factor as Fraïssé limits of suitable classes of structures. Moreover by means of Fraïssé theory we provide new examples of AF algebras with strong homogeneity properties. As a consequence of our analysis we deduce Ramsey-theoretic results about the class of full-matrix algebras.